M205. LONG-TERM SAFETY OF LUMATEPERONE (ITI-007): METABOLIC EFFECTS IN A 1-YEAR STUDY. (18th May 2020) - Satlin, Andrew; Durgam, Suresh; Vanover, Kimberly E; Davis, Robert E; Huo, Jason; Mates, Sharon; Correll, Christoph
Abstract: Background: Standard of care (SOC) treatments for schizophrenia are often associated with a spectrum of metabolic adverse effects including weight gain and increased risk of diabetes, hyperlipidemia, and hypertension. Identifying new schizophrenia treatments with a favorable weight gain and metabolic side effect profile is important in reducing patient morbidity, mortality, and improving patient outcomes Lumateperone (lumateperone tosylate, ITI-007) is a mechanistically novel agent for the treatment of schizophrenia that simultaneously modulates serotonin, dopamine, and glutamate neurotransmission. This distinct pharmacological profile may confer favorable tolerability with a low risk of adverse metabolic effects compared with SOC treatment. In 3 short-term trials in patients with acute exacerbation of schizophrenia, lumateperone was associated with minimal weight gain and few metabolic side effects. This analysis of a phase 3 open-label study evaluated the weight change and metabolic profile of lumateperone in patients with stable schizophrenia that were switched from SOC to lumateperone 42-mg treatment (ITI-007 60 mg) for up to 1 year. Methods: The metabolic profile of lumateperone was evaluated in prospective and post hoc analyses of an open-label study (Study 303). This study comprised patients with stable schizophrenia that were switched from SOC treatment to lumateperone 42 mg for 1 year of treatment; the study is currently ongoing to evaluate patients with greater than 1-year lumateperone exposure. Change in weight and metabolic assessments were conducted in all patients who completed 1 year of treatment and in patients who were classified at baseline by body mass index (BMI) as overweight (BMI 25–30) or obese (BMI ≥30). Results: In the 1-year open-label study, 602 patients received at least 1 dose of lumateperone 42 mg and were included in the safety population; 239 patients completed 1 year of treatment. Mean cholesterol (total and low-density lipoprotein [LDL]) significantly decreased from SOC baseline (total: −11.4 mg/dL, P<.001; LDL: −10.2 mg/dL, P<.001). Significant improvements in mean body weight from SOC baseline were observed during the 1-year lumateperone treatment (−2.1 kg, P<.001). Lumateperone treatment was also associated with significant reductions from SOC baseline in BMI (−0.67 kg/m2, P=.002) and waist circumference in both men (−3.21 cm, P<.001) and women (−3.28, P<.001). Potentially clinically significant (PCS; ≥7% change from baseline) weight loss occurred in 19% of the population. Similarly, a high percentage of obese (19%) and overweight patients (21%) showed PCS weight decrease from SOC baseline. Conversely, PCS weight gain was infrequent in all patients (5%) and in obese (4%) and overweight (3%) patients. Shift from overweight to normal BMI occurred in 28% of patients; shift in BMI from overweight to obese occurred in 4% of patients. Improvement in BMI from obese to overweight was observed in 21% of patients. Discussion: In patients switched from SOC treatment, improved metabolic and weight parameters were observed following 1 year of treatment with lumateperone 42 mg. Marked improvements were seen in patients that were overweight or obese at SOC baseline. These results suggest that lumateperone 42 mg may be a promising new treatment for schizophrenia, with minimal metabolic risk.